2017
DOI: 10.1080/19476337.2017.1337048
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining orange juice–maltodextrin powders without structure collapse based on the glass transition temperature and degree of polymerization

Abstract: Urizar (2018) Obtaining orange juice-maltodextrin powders without structure collapse based on the glass transition temperature and degree of polymerization, CyTA -Journal of Food, 16:1, 61-69, DOI: 10.1080/19476337.2017 To link to this article: https://doi.org/10. 1080/19476337.2017 A set of four maltodextrins (MXs) with different degree of polymerization were employed as carrying agents for the spray drying of liquid orange juice (OJ) without collapse in the microstructure; this was visually observed as fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…In general, Tg was observed superimposed with first order transitions, such as the evaporation temperature of water (Tv) around 80 °C, the degradation of low molecular weight sugars (glucose, sucrose, fructose) in a range of 141–153 °C, and the degradation of high molecular weight sugars (maltodextrin) in a range of 175–260 °C. The aforementioned thermal events coincide with those reported by Saavedra Leos et al [ 27 ] and [ 28 ]. Table 1 summarizes the results of the thermal events determined from the MDCS thermograms for each of the SJ-MX powders.…”
Section: Resultssupporting
confidence: 91%
“…In general, Tg was observed superimposed with first order transitions, such as the evaporation temperature of water (Tv) around 80 °C, the degradation of low molecular weight sugars (glucose, sucrose, fructose) in a range of 141–153 °C, and the degradation of high molecular weight sugars (maltodextrin) in a range of 175–260 °C. The aforementioned thermal events coincide with those reported by Saavedra Leos et al [ 27 ] and [ 28 ]. Table 1 summarizes the results of the thermal events determined from the MDCS thermograms for each of the SJ-MX powders.…”
Section: Resultssupporting
confidence: 91%
“…The final properties of the spray-drying products containing MXs also depend on the equivalent of dextrose (DE). Saavedra-Leos et al [45] reported the spray drying of a set of MXs with different DE values. Concentrated solutions containing 30% of dissolved solids were spray dried at an inlet temperature of 200 • C. The obtained powders presented a white appearance.…”
Section: Microencapsulation Of Food Active Ingredientsmentioning
confidence: 99%
“…Saavedra-Leos et al determined an inverse relation between T g and DE of maltodextrins [21]. Through several works reported by the Saavedra-Leos group [14,22,37,38,39], we have observed that in some juices such as orange and blueberries, their physicochemical properties varied with the differences in the type and distribution of molecular weight of the carrier agent. In these studies, we have attributed this behavior mainly to: (i) Differences in the molecular weight distribution of the carrier agent, (ii) the arrangement of polymer chains (i.e., entangled or linear) and (iii) the type of molecule in these chains (for example, glucose for maltodextrin or fructose for inulin).…”
Section: Resultsmentioning
confidence: 72%